Minimizing dark current in lead halide perovskite photodetectors - Yuping Liu; Zhirong Liu; Haixian Yu; Junyi Huang; Xiongjie Li; Xiaoting Ma; Yan Shen; Guoli Tu; Mingkui Wang (Chemistry of Inorganic Materials, 2023)
Photodetector is an essential component in many optoelectronic devices nowadays that converts the incoming optical signal into an electrical signal. The need for multi-spectral photoelectric detection in the same scene promotes the application of wide spectrum detection. Halide hybrid perovskites can be excellent candidates for wide-spectrum photodetectors which cover a spectral range of UV–visible–infrared. However, the intrinsic defects of perovskite material and the defects among various functional layers might increase the dark current and seriously reduce the photodetector device optoelectronic performance. Therefore, reducing the dark current and improving the spectra-detection performance of ultra-wideband radiation perovskite photodetectors are the main targets for investigation of high-efficient perovskite photodetectors. In this mini-review, the parameters that determine the dark current of perovskite photodetectors and their effects on the device performance are discussed for the first time. Then this work evaluated the promising approaches to solve the defect-dependent recombination in perovskite photodetectors. We further outlooked the effective approaches for perovskite photodetectors for wide-spectrum application.